1980
DOI: 10.1159/000207252
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Iron Stores in Subjects Heterozygous for β-Thalassaemia Based on Serum Ferritin Levels

Abstract: Serum ferritin concentration was assessed in male and female pregnant and non-pregnant thalassaemia carriers and in normal subjects of both sexes. Low ferritin levels were found in 61% of non-pregnant and in 32% of pregnant female β-thalassaemia heterozygotes whereas male thalassaemia carriers had normal iron stores. Increased ferritin levels were not observed in any of the subjects examined. These findings show that iron deficiency is a common finding in female thalassaemia carriers of reproductive age who ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…As the sample population mostly consists of mothers accompanying their children suffering from b thalassemia to the daycare unit of hematology department of NRS Medical College and hospital, the number of females in the study outnumbers the males. Similar study has been conducted in the past showing iron deficiency a common finding in female TT of reproductive age not receiving iron supplementation [7]. The findings here suggest that iron deficiency is a common co-existing condition in beta TT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As the sample population mostly consists of mothers accompanying their children suffering from b thalassemia to the daycare unit of hematology department of NRS Medical College and hospital, the number of females in the study outnumbers the males. Similar study has been conducted in the past showing iron deficiency a common finding in female TT of reproductive age not receiving iron supplementation [7]. The findings here suggest that iron deficiency is a common co-existing condition in beta TT.…”
Section: Discussionsupporting
confidence: 89%
“…Conflicting data then came up regarding the iron metabolism in TT. In 1987 Economidou et al [7] presented their study ''assessment of iron stores in subjects heterozygous for beta-thalassemia based on serum ferritin levels.'' which showed that iron deficiency was a common finding in female TT of reproductive age not receiving iron supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise the cumber someness of this test, as compared with the simplicity of serum ferritin assays, makes it the last one to choose for detecting early iron overload. (3) The influence of population differences in the iron content of the diet or in the frequency of idiopathic hemochroma tosis (1H) might also explain why in some countries beta-thalassemia trait subjects run a higher risk of developing iron overload than in others [8,17], Population differ ences may be also responsible for the con flicting results between ours and those of some Italian authors who studied Sardinian subjects. This discrepancy could possibly be due to the fact that Sardinians have a defi nitely different ethnic origin from other con tinental Italians.…”
Section: Discussionmentioning
confidence: 74%
“…(2) Many investigators have studied the iron status of beta-thalas semia trait by evaluation of serum iron now considered one of the least sensitive indices [8,9], Moreover, serum ferritin was seldom measured and probably never at the same time as the desferrioxamine test [7,17]. Many of our subjects had high serum ferri tin levels at times when serum iron and transferrin saturation were still in the nor mal range.…”
Section: Discussionmentioning
confidence: 95%
“…Some investigators have found normal iron store reflected by measurement of serum ferritin level 6 , others have reported that b-thalassemia traits are frequently in positive iron balance and are at high risk of developing iron overload [7][8][9] . If severe iron overload has been described in a group of patients with thalassemia trait then administration of iron to these cases can actually be proved harmful and produce the complication of iron.…”
Section: Bangladesh J Medicine 2014; 25 : 13-16mentioning
confidence: 99%